Cross-cultural L2 learning exchange: A qualitative examination of strategies, tools, cognition and translation outcomes - Robert W. Elliott; Xiaolei Chen (Institute of Advanced Engineering and Science, 2019)
Amidst the milieu of free and at-cost L2 language software applications coming into existence for use on mobile devices and computers, adult L2 learners are faced with the challenge of selecting their best choice for them to use in acquiring a specific second language. Their selection is based on their individual need and the context in which they plan to use the second language. More importantly, it is well known there is no single tool, resource, or strategy that adult L2 learners can use to fully acquire a second language quickly and effectively, especially for intercultural couples who lack a common language for daily communication. While there is much literature on the topic of L2 acquisition and learning, the purpose of this auto-ethnographic study is to share with readers specific aspects of our journey in acquiring each other’s native language throughout their first year together. Included are subsequent findings involving cognition and translation issues as developing skills recognized during various phases of L2 acquisition.